Use of radionuclide studies in the preparation of patients for liver transplantation and in the postoperative period - M. Sh. Khubutia; N. E. Kudryashova; O. G. Sinyakova; I. V. Aleksandrova; E. I. Pervakova; O. I. Andreitseva; A. V. Chzhao (Трансплантология (Москва))
The data summarized in this review suggest that radionuclide studies are highly effective in the clinical situations that the structure and function of the liver should be simultaneously evaluated, which is in full measure appropriate for liver transplantation.